2011
DOI: 10.1007/s10843-010-0071-9
|View full text |Cite
|
Sign up to set email alerts
|

Behaviours and entrepreneurial intention: Empirical findings about secondary students

Abstract: Entrepreneurial intention, Entrepreneurship education, Secondary students,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
2
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(180 citation statements)
references
References 30 publications
11
136
2
15
Order By: Relevance
“…Similarly, we found a positive effect of entrepreneurial self-efficacy on social entrepreneurial intention. Our results were consistent with other empirical investigations, supporting the important role of self-efficacy as a predictor of both entrepreneurial intentions (Paço et al, 2011;Shook & Bratianu, 2008) and social entrepreneurial intentions (Urban & Teise, 2015). Some researchers (Krueger & Brazeal, 1994; An examination of certain antecedents of social entrepreneurial intentions among Mexico residents Urban & Teise, 2015) consider self-efficacy as a fundamental factor among potential and novice entrepreneurs.…”
Section: Theoretical Implicationssupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, we found a positive effect of entrepreneurial self-efficacy on social entrepreneurial intention. Our results were consistent with other empirical investigations, supporting the important role of self-efficacy as a predictor of both entrepreneurial intentions (Paço et al, 2011;Shook & Bratianu, 2008) and social entrepreneurial intentions (Urban & Teise, 2015). Some researchers (Krueger & Brazeal, 1994; An examination of certain antecedents of social entrepreneurial intentions among Mexico residents Urban & Teise, 2015) consider self-efficacy as a fundamental factor among potential and novice entrepreneurs.…”
Section: Theoretical Implicationssupporting
confidence: 92%
“…Self-efficacy is one of the fundamental prerequisites for potential entrepreneurs (Krueger & Brazeal, 1994), given that in certain contexts most novice entrepreneurs do not have enough business experience (Luthans & Ibrayeva, 2006). Results from empirical investigations have shown that self-efficacy is a predictor of entrepreneurial intention (Barbosa, Gerhardt, & Kickul, 2007;Paço, Ferreira, Raposo, Rodrigues, & Dinis, 2011;Shook & Bratianu, 2008). Similarly, research has also shown that self-efficacy is one of the factors that best explain social entrepreneurship intentions (Urban & Teise, 2015).…”
Section: H6: Subjective Norms Would Have a Positive Effect On Social mentioning
confidence: 99%
“…market challenges, risk taking). In addition, [13] pointed that TPB was an appropriate tool to model the development of entrepreneurial intention through pedagogical processes and learning in among students in Portugal. Meanwhile, [14] defined entrepreneurial intention as a mental orientation such as desire, wish and hope which influence their choice of entrepreneurship.…”
Section: Entrepreneurial Intentionmentioning
confidence: 99%
“…Thus, in entrepreneurship education literature, primary and secondary school has received growing attention and enterprise education programmes in secondary school were confirmed to be important for later entrepreneurial intentions. It is believed that the ideal stage to acquire basic knowledge about entrepreneurship and to foster a positive attitude towards entrepreneurship is during childhood and adolescence years Paço et al, 2011a;Paço et al, 2011b).…”
Section: Literature Reviewmentioning
confidence: 99%